The Effectiveness of Folklore based Animation Video in Enhancing Students’ Speaking Skill - Lulu Jola Uktolseja; Abraham Manuhutu; Jalmijn Tindage (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
English as a compulsory subject at school, is often a scourge for students. This has become a common conflict that occurs in schools. In this case, the work of the teacher is urgently needed to convey learning in a needs-based manner. Teachers do not only design lessons according to lesson plans, but they also need to be able to design lessons creatively to foster positive habits that directly improve learners' English skills. The purpose of this research is to analyze the effectiveness of learning English using two-dimensional animation media, especially folklore from the Papua region, one of which is from Tambrauw Regency. The design of this research is Classroom Action Research (CAR). The sample of this research is 25 students of 1st Semester English Education Study Program at Universitas Victory Sorong who learn in English Club. The results of the research showed that: (1) Based on observations, students will become more interested and confident in speaking English. (2) Based on the test, there is a very large change in the positive direction compared to a very good value of 36% in cycle 1, but in cycle 2 it is 84%, an increase of 48%. This folklore-based animated video worked well and met the needs of students in the first semester of the English Club.